2009
DOI: 10.1128/mcb.01517-08
|View full text |Cite
|
Sign up to set email alerts
|

Association of C-Terminal Ubiquitin Hydrolase BRCA1-Associated Protein 1 with Cell Cycle Regulator Host Cell Factor 1

Abstract: Protein ubiquitination provides an efficient and reversible mechanism to regulate cell cycle progression and checkpoint control. Numerous regulatory proteins direct the addition of ubiquitin to lysine residues on target proteins, and these are countered by an army of deubiquitinating enzymes (DUBs). BRCA1-associated protein-1 (Bap1) is a ubiquitin carboxy-terminal hydrolase and is frequently mutated in lung and sporadic breast tumors. Bap1 can suppress growth of lung cancer cells in athymic nude mice and this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
214
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(222 citation statements)
references
References 51 publications
8
214
0
Order By: Relevance
“…Although BAP1 can promote cell proliferation by accelerating G1/S progression via host cell factor-1 activation 52,53 , our results suggest that BAP1 can also contribute to cell proliferation by promoting replication fork progression. Indeed, BAP1 depletion results in an accumulation of cells in S phase; conversely, BAP1 re-expression in BAP1-null cells reduces cells in S phase 18,53,54 . Thus, the impact of BAP1 on cell proliferation appears to manifest as the combined effects on DNA replication and other cellular pathways that control cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%
“…Although BAP1 can promote cell proliferation by accelerating G1/S progression via host cell factor-1 activation 52,53 , our results suggest that BAP1 can also contribute to cell proliferation by promoting replication fork progression. Indeed, BAP1 depletion results in an accumulation of cells in S phase; conversely, BAP1 re-expression in BAP1-null cells reduces cells in S phase 18,53,54 . Thus, the impact of BAP1 on cell proliferation appears to manifest as the combined effects on DNA replication and other cellular pathways that control cell cycle progression.…”
Section: Discussionmentioning
confidence: 99%
“…We next sought to examine the subcellular localization of these two proteins and determine whether they could colocalize together within cells. Although several previous studies have shown that a short form of the MLL5 proteins (1-560 amino acids) was located mainly in the cell nucleus (20), and the HCF-1 has been detected primarily in the nucleus (30,31,(33)(34)(35)(36)(37)(38)(39), whether they are able to colocalized within the cell nucleus has not been well investigated. To address this, HeLa cells were transiently co-transfected with plasmids encoding HCF-1 protein and FLAGtagged MLL5 protein.…”
Section: Identification Of Mll5-associated Proteins Bymentioning
confidence: 98%
“…For example, HCF-1 is known to interact with a number of histone-modifying enzymes (39), so deubiquitination of histone H2A by BAP1 could create a different environment for these chromatin regulators. Alternatively, given that BAP1 can deubiquitinate HCF-1 (14,15), it is possible that BAP1 remodels HCF-1 complexes, potentially regulating recruitment of histone-modifying enzymes. Although this study did not find a critical function of HCF-1 at the FoxK2 target genes, further studies will be needed to fully understand the role of the BAP1⅐HCF-1 complex in gene regulation.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, BAP1 has been shown to deubiquitinate two BAP1-interacting proteins, HCF-1 (a transcription coregulator) and O-linked N-acetylglucosamine transferase (13)(14)(15). However, the biological significance of this deubiquitination has not been established.…”
mentioning
confidence: 99%